Water and methanolic extracts of Salvia officinalis protect HepG2 cells from t-BHP induced oxidative damage - Lima, Cristóvão F. (2007)
Common sage (Salvia officinalis L., Lamiaceae) is an aromatic and medicinal plant well known for its antioxidant properties. Some in vivo studies have shown the biological antioxidant effects of sage. However, the intracellular antioxidant mechanisms of action are still poorly understood. In this study, we evaluated the cytoprotective effects of two sage extracts (a water and a methanolic extract) against tert-butyl hydroperoxide (t-BHP)-induced toxicity in HepG2 cells. The most abundant phenolic compounds present in the extracts were rosmarinic acid and luteolin-7-glucoside. Both extracts, when co-incubated with the toxicant, protected significantly HepG2 cells against cell death. The methanolic extract, with a higher content of phenolic compounds than the water extract, conferred better protection in this in vitro model of oxidative stress with liver cells. Both extracts, tested in a concentration that protects 80% against cell death (IC80), significantly prevented t-BHP-induced lipid peroxidation and GSH depletion, but not DNA damage assessed by the comet assay. The ability of sage extracts to reduce t-BHP-induced GSH depletion by 62% was probably the most relevant contributor to the observed cytoprotection. A good correlation between the above cellular effects of sage and the effects of their main phenolic compounds was found. When incubated alone for 5 h, sage extracts induced an increase in basal GSH levels of HepG2 cells, which indicates an improvement of the antioxidant potential of the cells. Compounds present in sage extracts other than phenolics may also contribute to this latter effect. Based in these results, it would be of interest to investigate whether sage has protective effects in suitable in vivo models of liver diseases, where it is known that oxidative stress is involved.